Comparative Assessment Of Plasma Concentrations Of Mycophenolate Mofetil Capsules With Respect To Its Pure Form In Mammalian Rodent (Oryoctolagus Cuniculus) Using UV-Spectrophotometry - DR. K. L. SENTHIL KUMAR; M. HEMANTH KRISHNA (International Journal of Pharma and Bio Sciences, 2011)
The present study involves the determination of the plasma concentration of Mycophenolate mofetil (MMF) by performing biological sample analysis of the plasma sample of rabbit using UV-Visible spectrophotometer and comparative study of the MMF in capsules with reference to the standard MMF. The plasma concentration of pure MMF and MMF in marketed capsules after administering a single oral dose were determined individually and the percentage relative plasma concentration of MMF in capsule with reference to that of the pure MMF at all the predetermined time intervals were found out in respect of comparative study. The plasma concentration of the standard MMF and MMF in capsule at different time intervals were found out. The mean maximum plasma mycophenolate mofetil concentration (Cmax) after a mycophenolate mofetil 100 mg dose in healthy rabbits was 43.67 µg/ml for reference MMF and 42.67 µg/ml for sample MMF in capsule formulation occurred at 1 hour postdose, decayed with a mean apparent half-life (t1/2) of around 16 hours. Relative plasma concentration of sample with reference standard at peak concentration at one hour was found to be 102.34%.